PENTINGNYA PENGOLAHAN BASAH (WET PROCESSING) BUAH KOPI ROBUSTA (Coffea robusta Lindl.ex.de.Will) UNTUK MENURUNKAN RESIKO KECACATAN BIJI HIJAU SAAT COFFEE GRADING - Ayu Rahmawati Sulistyaningtyas (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Coffee plant (Coffea.sp) is one of the main commodities in Indonesia. The types of arabica coffee (Coffea arabica) androbusta coffee (Coffea robusta) are the most widely cultivated species. In Indonesia, coffee plantations began to grow rapidly so that potential for the development of domestic coffee. The development of the people's coffee plant required support of various factors such as availability of facilities, methods of processing and postharvest handling which suitable for the coffee plantations to produce quality coffee beans according to Indonesian National Standard (SNI).Coffee fruit should be handled quickly into a more stable form to be safe to store for a certain period of time. The seedquality criteria covering physical aspect, taste and hygiene and uniformity and consistency aspect is determined by thetreatment at each stage of production process. The result of overview study showed that  the handling of harvest, postharvest and coffee processing at farmers level should be done effectively and efficiently. During pulping process, coffee skin has exfoliated from their fruit. This process caused grean bean rubbing against pulper tools. So, wet processing may potentially reduced a risk of defect robusta green beans. In conclusion, wet processing robusta fruit (Coffea robusta Lindl.Ex.De.Will) is important to reduce the risk of green seed defects during coffee grading process.Keywords: Coffea, robusta, biji,pengolahan,basah, resiko, cacat